(untitled) (Conferencea, 2024)
Demographic policy is one of the main determinants of the security of states and, therefore, of world politics. In the demographic process, political-legal relations are formed into institutional forms of national security. For 11 years in Georgia, demographic security issues have been reflected in almost all high-level political documents. These documents will be reviewed in a scientific article. We would also like to review the role of demographic policy and the expected processes in world politics insecurity issues.